Precise Modeling and Simulation Analysis of the Straight Bevel Gear Train - Xiao Hua; Xie Moyan; Chen Guansheng (Jixie chuandong)
In order to investigate the influence of the straight bevel gear train on a robot joint,several methods of straight bevel gear modeling are compared in accuracy grade and operating convenience. And then the principle of the formation of spherical involute is chosen to build a straight bevel gear train geometry model accurately and parametrically with the use of Pro / E. Based on this model,its dynamics simulation and finite element analysis are carried out in ADAMS,Hyper Mesh and ABAQUS separately. The results show that the model is in conformity with theory and the accuracy of modeling and the feasibility of simulation are verified,a foundation for further study on the robot joint and other similar institutions is provided.